Handbook of Solid State Chemistry 2017
DOI: 10.1002/9783527691036.hsscvol4029
|View full text |Cite
|
Sign up to set email alerts
|

Materials for Tissue Engineering

Abstract: Surgical procedures based on tissue engineering ( TE ) are used every day to reconstruct damaged or diseased tissues. These approaches look for the regeneration of living tissues by combining cells from the body with highly porous scaffold biomaterials decorated with biologically active molecules, signals, which act as templates for tissue regeneration to guide the growth of new tissue. This chapter describes the general concepts and main applications in which TE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…The spectrum shows bands at 475, 575, 966, 1090-1220 and 3370 cm −1 , attributed to stretching modes of phosphate and O-H functional groups, respectively (Figure 3a). The stretching band of C=O of the CO 3 2− group at 1660 cm −1 indicates the incorporation of carbonate in apatite structure that could improve the absorption or catalytic activity of HAp. To prove that the carbonate, phosphate and hydroxyl sites on the catalyst are stable after each run of recyclability, we obtained the FT-IR spectrum of HAp after five runs ( Figure 3b) and compared with fresh HAp (Figure 3a).…”
Section: Op Oetmentioning
confidence: 99%
“…The spectrum shows bands at 475, 575, 966, 1090-1220 and 3370 cm −1 , attributed to stretching modes of phosphate and O-H functional groups, respectively (Figure 3a). The stretching band of C=O of the CO 3 2− group at 1660 cm −1 indicates the incorporation of carbonate in apatite structure that could improve the absorption or catalytic activity of HAp. To prove that the carbonate, phosphate and hydroxyl sites on the catalyst are stable after each run of recyclability, we obtained the FT-IR spectrum of HAp after five runs ( Figure 3b) and compared with fresh HAp (Figure 3a).…”
Section: Op Oetmentioning
confidence: 99%
“…Then, a continuous flow of argon maintained at 100 l h À1 was injected inside the working tube resulting in an increase of the pressure to about 10 À2 mbar. Finally, the temperature was applied in two steps ( Figure 2b) according to the protocol proposed by Vallet-Regi and Gonzalez-Calbet: a first plateau at 120°C during 1 h for water evaporation followed by a second plateau at 1 000°C during 1 h. [18] The flow of argon was maintained during the whole thermal treatment until the complete cooling to room temperature.…”
Section: Thermal Treatment Under Controlled Atmosphere (Thuca)mentioning
confidence: 99%
“…Furthermore, the crystal face at which the HA crystal grows was reported to affect the macroscopic morphology and morphology transformation of HA particles such as needle-like, platelet-like or spherical morphologies. [16,17] Accordingly, it can be supposed that the exposed crystal faces might be different on various shapes of HA particles. Recently, we found that rod-shaped HA (r-HA) particles could fuse with spherical HA (s-HA) particles during sintering, thus leading to enhanced compressive strength of the porous HA scaffolds.…”
Section: Introductionmentioning
confidence: 99%